Hypoglycemic Coma in a Hemodialysis Patient Receiving Blood Glucose-Lowering Therapy With the Single Agent Teneligliptin. Issue 11 (19th March 2018) - Minezumi, Takumi; Takeda, Shin-ichi; Igarashi, Yusuke; Sato, Kentaro; Murakami, Yoshiaki; Nagata, Daisuke
Blood glucose management in patients undergoing dialysis is clinically challenging. In this population, most conventional oral hypoglycemic agents are contraindicated, especially from the perspective of pharmacokinetics. Dipeptidyl peptidase-4 inhibitors exert unique pharmacologic actions via glucose-dependent mechanism and have an excellent tolerability profile with a very low risk of hypoglycemia. Furthermore, the literature reports that some dipeptidyl peptidase-4 inhibitors such as teneligliptin can be administered at the usual dose, regardless of a patient's level of renal impairment. In this article, we report a case of hypoglycemic coma with a blood glucose level of 23 mg/dL. The patient became fully conscious shortly after receiving a glucose injection; however, severe hypoglycemia recurred for approximately 1.5 days. It eventually disappeared on the discontinuation of teneligliptin, which was the only antidiabetic agent that he had received. The present case may provide deep insights into promoting the safe use of hypoglycemic agents in patients undergoing dialysis.